New Trends In Efl Online Learning And Teaching Through The Lens Of Artificial Intelligence - زيتوني خديجة سميرة (مجلة المقدمة للدراسات الانسانية و الاجتماعية, 2022)
This paper attempts to tackle new ideas concerning the utilization of Artificial Intelligence (AI) in online EFL learning in higher education. It hypothesizes that introducing AI in EFL online learning will optimize the quality of learning and guarantee its success. The study aims to shed lights on the importance of AI in online learning and unveils its pros and cons. In this regard, qualitative descriptive research was carried out. A questionnaire and an opinionnaire were administered to teachers and learners from the English department at Barika University center. The findings collected reveal that AI apps have a salient role in facilitating and ameliorating the EFL learning/teaching process. These apps will, for sure, improve the quality and success of online learning. Therefore, the study at hand highlights the potentiality of AI in reducing the online learning barriers and challenges and enhancing the learning outcomes.